Effects of biochar and barley straw application on the rice productivity and greenhouse gas emissions of paddy field - Kang, Se-Won; Yun, Jin-Ju; Park, Jae-Hyuk; Cheong, Yong Hwa; Park, Jong-Hwan; Seo, Dong-Cheol; Cho, Ju-Sik (Applied biological chemistry, 2021)
To improve the agricultural environment, utilization of biochar and organic materials from paddy fields gaining importance. This is because the long-term use of inorganic fertilizers aggravates the soil environment, and also because rice paddy is a major source of CH 4 and N 2 O emissions during rice cultivation which involves continuous flooding. Recently, the application of organic materials and biochar to the soil has received increasing attention due to their potential benefits related to soil quality, crop growth, and greenhouse gas emission. This study examines the influence of biochar and straw treatments on rice growth, soil physicochemical properties, and global warming potential in the paddy field. Five treatments were applied for the study: control (Cn), inorganic fertilizer (IF), barley straw biochar (BC), barley straw (BS), and BC + BS. Soil quality after rice harvesting improved in the BC treated group. The yield components of rice were also improved in the BC + BS, compared to other treatments. These effects resulted in increased rice yield and uptake of nutrient contents in the BC + BS treatment. Total fluxes of CH 4 and N 2 O relative to global warming significantly decreased by 37.3% and 65.2% in the BC + BS group than in the IF treatment, respectively. Consequentially, a cropping system with BC and BS is an effective strategy to improve rice productivity and soil quality and also reduce GHG emissions from paddy fields, thereby alleviating global warming.